The Effectiveness of Integrating Scientific Nutrition Education into Physical Education on Nutrition Knowledge and Healthy Behavior Intentions among Junior High School Students - Zhao Shuai; Ni Nyoman Parwati; I Gde Wawan Sudatha (Jurnal Paedagogy, 2026)
This study aims to analyze the effectiveness of an experimental approach integrating scientific nutrition education into physical education learning in improving nutrition knowledge and healthy behavior intentions among junior high school students. The study used a quasi-experimental design with a pretest–posttest control group model, involving 40 seventh-grade students at Beijing No. 3 Middle School (Xicheng District, Beijing, China) who were divided into an experimental group and a control group through class-based randomization. The experimental group followed an integrated "physical training + scientific nutrition" curriculum for 10 weeks, while the control group received conventional physical education. The research instruments included nutrition knowledge tests and healthy behavior intention questionnaires that met the criteria for validity and reliability. Data analysis was performed using Multivariate Analysis of Covariance (MANCOVA) as the main analysis, followed by univariate ANCOVA, to control for differences in students' initial abilities. The results of the multivariate analysis of covariance (MANCOVA) indicated a significant multivariate effect of the teaching mode on students’ nutrition knowledge and healthy behavior intention after controlling for pretest scores (Wilks’ Λ = 0.338, F = 34.21, p < 0.001). This finding provides quantitative evidence that the integrated physical training and scientific nutrition learning approach significantly improved students’ learning outcomes compared to the conventional physical education model. These findings indicate that integrating scientific nutrition concepts into authentic physical training experiences can build strong links between cognitive understanding, physical experience, and health behavior reflection. This study concludes that the integration of scientific nutrition education based on educational technology is an effective and strategic approach to improving health literacy and encouraging sustainable healthy behavior change among junior high school students.